Spontaneous clostridial myonecrosis after pregnancy – emergency treatment to the limb salvage and functional recovery: a case report. Issue 1 (13th September 2012) - De Angelis, Barbara; Cerulli, Paolo; Lucilla, Lucarini; Fusco, Augusto; Di Pasquali, Camilla; Bocchini, Ilaria; Orlandi, Fabrizio; Agovino, Annarita; Cervelli, Valerio
<x xml:space="preserve">Abstract</x> Clostridial myonecrosis (CM) is a rare, life threatening necrotizing infection of a skeletal muscle caused by Clostridium perfringens in the majority of cases. The diagnosis may be difficult because of few diagnostic and cutaneous signs early in its course. Standard therapy involves surgical debridements of a devitalized tissue and high‐dose organism‐specific antibiotic therapy. The hyperbaric oxygen has also showed its usefulness in the treatment of these infections. Autograft systems as tissue replacement, based on bioengineered materials, have been demonstrated to be safe and effective treatments for chronic wounds and a suitable physiotherapy is recommended for the recovery of functional impairments of upper extremities. We present a rare case of CM of right upper limb treated with a combination of standard treatments and new techniques.